Familial Mediterranean Fever in Chinese Children: A Case Series - Ji Li; Wei Wang; Linqing Zhong; Junyan Pan; Zhongxun Yu; Shan Jian; Changyan Wang; Mingsheng Ma; Xiaoyan Tang; Lin Wang; Meiying Quan; Yu Zhang; et al. (Frontiers Media S.A., 2019)
Background: Familial Mediterranean fever (FMF) is an inherited auto-inflammatory disorder and is extremely rare in Chinese. This study aimed to investigate the demographic, clinical, and genetic features of FMF in a series of Chinese pediatric patients.Methods: This was a retrospective case series of children with recurrent febrile or inflammatory episodes and referred to the Peking Union Medical College Hospital between 06/2013 and 06/2018. All suspected patients were genetically diagnosed and met the Tel-Hashomer criteria for FMF. Demographic, clinical, genetic, and treatment characteristics were collected. Descriptive statistics were used.Results: Eleven patients were included (seven boys and four girls). The median age at the time of disease onset was 7.1 (range, 3-12) years, while the median age at diagnosis was 10.9 (range, 6-15) years. The median delay in diagnosis was 2.1 years (range, 6 months to 6.7 years). Fever (100%, 11/11) was the most common symptom, followed by joint pain (63.6%, 7/11), rash (54.5%, 6/11), abdominal pain (36.4%, 4/11), and oral ulcers (18.2%, 2/11), without evidence of amyloidosis. C-reactive protein (81.8%, 9/11) and erythrocyte sedimentation (90.9%, 10/11) were increased during attacks. All patients harbored one to five different MEFV mutations, with E148Q and L110P being the most frequent. A novel non-synonymous mutation F636Y in exon 10 was discovered. Favorable responses to colchicine was observed in all six treated patients.Conclusion: The most common variants in our study were E148Q and L110P. F636Y may found for the first time. Colchicine led to favorable responses in all treated patients.